Analisis Perilaku Konsumen Terhadap E-Commerce Dibidang Fashion - Hasibuan, Diva Viola Natasya; Chintya, Neha; Ramadhana, Royhan Zaki; Situmorang, Daffa Chaindana Zein; N, Nurbaiti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Technological developments and E-commerce have changed consumer behavior in the fashion industry in Indonesia. Consumers are now more critical and informed in making purchasing decisions, influenced by product quality, price, promotions and technological innovation. Social media also plays an important role in shaping consumer preferences through trends and influencer recommendations. On the other hand, this research aims to analyze the influence of digital transformation on consumer behavior, opportunities and challenges faced by fashion businesses. This research identifies several factors that influence consumer purchasing decisions, such as trust in e-commerce platforms, price, promotions, social media influence, product quality, and user experience. Consumer trust in transaction security and platform reputation are key to e-commerce success. Apart from that, competitive prices, promotions, and the influence of trends through social media also influence purchasing decisions. Rapid changes in fashion trends are influenced by developments in digital technology and online consumption. Even though this sector is growing rapidly, the challenges for MSMEs are still large, especially in terms of adapting to digital technology. The digital economic era offers great opportunities, but also requires adjustments to marketing and distribution strategies for business actors, especially MSMEs, to remain competitive. The method used in this research is qualitative, namely by observation and consumer interviews. The research results are expected to provide strategic insight for industry players in increasing competitiveness in the digital era.